RELEVANSI SIKAP BERAKUNTANSI PELAKU UMKM MUDA DAN PENGGUNAAN INFORMASI AKUNTANSI TERHADAP KEBERHASILAN USAHA - Ayu Dwidyah Rini; Kazia Laturette (Universitas Negeri Malang, 2016)
The effect of accounting attitude young SMEs and the use of accounting information to business success. Accounting is an information system that produces financial information to the parties involved in economic activities. This study aims to determine the relationship accounting attitude and use of accounting information businesses small and medium micro young to business success . Data was collected through questionnaires with 100 young SMEs in Surabaya . The study uses a quantitative approach with multiple linear regression analysis and snowball sampling to sampling. The results of the study explained that the accounting attitude young SMEs , accounting information has a significant relationship in partial to business success. The results also explain that the accounting information has a dominant influence on the success of young SME business in Surabaya.Keywords : Accounting Information , Attitude, Business Success